Analisis Kompetensi 4C melalui Model Pembelajaran Kooperatif Tipe Quantum Learning pada Pembelajaran Bahasa Indonesia Kelas IV di MIN Kudus - Izzah, Faiqotul; Herwani, Suci (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research aims to determine the application of 4C competencies as well as inhibiting and supporting factors in implementing 4C competencies through the Quantum Learning learning model. This research uses a qualitative descriptive method, with data collection carried out through interviews, observation, and documentation, as well as data analysis by reduction, data presentation, and drawing conclusions. The research results show that the application of 4C competencies through the Quantum Learning learning model in Indonesian language learning in class IV MI N Kudus consists of three stages, the planning stage for educators to prepare teaching modules and learning model steps. The implementation stage of educators uses TANDUR steps, and evaluation through formative, summative, competency and observation assessments. The factors inhibiting the application of 4C competencies from students are difficulty expressing opinions and lack of confidence when discussing, and from educators who need to adapt to various learning models. Meanwhile, supporting factors for 4C competency include active learning models, stimulation of creativity, delivery of material that is interesting and easy to understand.